Integrasi Pembelajaran dengan ICT di Sekolah Dasar Menuju Ciri Khas Pembelajaran Abad 21 - Ifrah Muliyani E. Pulungan; Eka Sustri Harida (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
The application of ICT in learning in elementary schools is one of the important strategies to improve the quality of education and digital competence of students. ICT allows for a more interactive, collaborative learning process, and focuses on developing critical thinking, creative, and communication skills. This study aims to analyze the role of ICT-based learning media in increasing students' learning motivation, as well as provide an overview of its implementation in elementary schools. This research was carried out with a qualitative approach, with a qualitative descriptive type of research. This approach is used because the focus of the research is to understand the nature of the role of ICT-based learning media in the context of learning motivation. Data collection is carried out through literature studies, which involve analysis of secondary data sources, including books, scientific literature, research reports, essays, theses, dissertations, and print and electronic articles related to ICT learning media. The literature study method allows researchers to obtain ready-to-use and relevant data to provide a clear picture of the phenomenon being studied. The results of the study show that the application of ICT-based learning media can increase students' learning motivation through the use of interactive and creative technology, as well as create a learning environment that is fun and relevant to the development of the 21st century. The implementation of ICT also requires policy support, teacher training, and infrastructure development to ensure the effectiveness and sustainability of the use of technology in the learning process in elementary schools.